Thrombopoietin knock-in augments platelet generation from human embryonic stem cells - Zhang, Leisheng (Stem Cell Res Ther, 2018)
BACKGROUND: Refinement of therapeutic-scale platelet production in vitro will provide a new source for transfusion in patients undergoing chemotherapy or radiotherapy. However, procedures for cost-effective and scalable platelet generation remain to be established. METHODS: In this study, we established human embryonic stem cell (hESC) lines containing knock-in of thrombopoietin (TPO) via CRISPR/Cas9-mediated genome editing. The expression and secretion of TPO was detected by western blotting and enzyme-linked immunosorbent assay. Then, we tested the potency for hematopoietic differentiation by coculturing the cells with mAGM-S3 cells and measured the generation of CD43(+) and CD45(+) hematopoietic progenitor cells (HPCs). The potency for megakaryocytic differentiation and platelet generation of TPO knock-in hESCs were further detected by measuring the expression of CD41a and CD42b. The morphology and function of platelets were analyzed with electronic microscopy and aggregation assay. RESULTS: The TPO gene was successfully inserted into the AAVS1 locus of the hESC genome and two cell lines with stable TPO expression and secretion were established. TPO knock-in exerts minimal effects on pluripotency but enhances early hematopoiesis and generation of more HPCs. More importantly, upon its knock-in, TPO augments megakaryocytic differentiation and platelet generation. In addition, the platelets derived from hESCs in vitro are functionally and morphologically comparable to those found in peripheral blood. Furthermore, TPO knock-in can partially replace the large quantities of extrinsic TPO necessary for megakaryocytic differentiation and platelet generation. CONCLUSIONS: Our results demonstrate that autonomous production of cytokines in hESCs may become a powerful approach for cost-effective and large-scale platelet generation in translational medicine. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13287-018-0926-x) contains supplementary material, which is available to authorized users.